Evaluation of the dao1 gene as a selectable marker in transformation of apple rootstock M26 as well as transformation of a vector containing GA20 oxidase gene into Agrobacterium - Larsson, Sara J. (2008)
The aim of this project was to evaluate the possibility to use D-alanine as a selective marker instead of commonly used antibiotics and herbicides in transformation of apple rootstock M26.